Roles and challenges of human resource management Funding and opportunities for human resource management in education - Yudaningsi, Nunik (Professorline, 2024)
Management of human resources, finances, and facilities is an essential aspect of training This paper aims to explore the role and challenges of managing these resources in the context of education in Indonesia The research method is a literature study, where secondary information from various sources is collected and analyzed The results showed that the management of personnel, finance, and facilities plays a strategic role in improving the quality, efficiency, and effectiveness of education However, managing these resources also comes with various challenges, such as lack of expertise, accountability, transparency, participation, and coordination among different stakeholders This article recommends several strategies to overcome these challenges, such as capacity building, implementation of quality standards, development of information systems, community empowerment, and synergy between government, private sector, and civil society.